Modelling of nonlinear viscoelastic creep behaviour of hot-mix asphalt. (1st October 2015) - Gao, Dongdong; Wang, Pengbin; Li, Ming; Luo, Wenbo
Highlights: The nonlinear viscoelastic creep behaviour of a hot-mix asphalt was investigated. The uniaxial compressive creep tests at different stress levels were conducted. The creep compliance magnitude and its increment decrease with applied stress. Three nonlinear models were employed and competitively evaluated. Abstract: The viscoelastic creep behaviour of a hot-mix asphalt (HMA) was experimentally investigated via uniaxial compressive creep tests subjected to eight given stress levels of 0.1–0.8 MPa. The tests lasting for 3600 s were conducted on a MTS 809 Axial/Torsional Test System at 26 °C. The experimental results demonstrate that the creep compliance magnitude and its increment within the steady state creep tend to decrease as the applied stress increases. The Findley model, the simplified multiple integral model and the modified time-hardening model were employed to describe the creep behaviour of the HMA within the first two creep stages, and then competitively evaluated by three criteria. The result shows that the Findley model is superior to the others. Moreover, it has been proved that the modified time-hardening model is a special case of the Findley model.